The problem with relying on dietary surveys: sociocultural correctives to theories of dietary change in the Pacific islands - McLennan, A; Shimonovich, M; Ulijaszek, S; Wilson, M (Taylor and Francis, 2018)
Background Dietary surveys are frequently used as the basis for theorising nutritional change and diet-related non-communicable disease emergence (DR-NCD) in the Pacific islands. However, findings from historical survey data do not always align with ethnographic evidence. Aims This paper aims to examine the extent to which the two types of evidence can lead to similar conclusions, and draw out the implications for current theories of, and interventions addressing, nutritional change. Subjects and methods Dietary surveys carried out on Nauru between 1927 and 1979 are reviewed and compared with ethnographic evidence documented by social researchers across the colonial and post-colonial periods. Results This comparison reveals several shortcomings of survey data. Nutritional issues considered to be relatively recent—such as high-fat, low-fibre diets and transition to imported foods—occurred a century ago in our analysis and point to a long history of nutrition policy and intervention failure. Further, there is limited evidence that caloric intake overall increased significantly over this period of time in Nauru. Conclusions Theories of dietary change and DR-NCD emergence and resulting interventions could be improved through a more holistic approach to nutrition that integrates sociocultural and historical evidence about both the target population and the scientists doing the research.